Regresi Faktor Curah Hujan, Kelembaban Udara, dan Hari Hujan terhadap Produksi Lada serta Alternatif Kebijakan di Sumatera Utara - Fransisca Natalia Sihombing; Koko Tampubolon; Triara Juniarsih (Agrinula : Jurnal Agroteknologi dan Perkebunan, 2020)
Introduction: This research was aimed to determine the relationship pattern of rainfall, humidity, and rainy day on the increase in pepper yield in North Sumatra. Materials and Methods: This research used the time-series data on factors of rainfall, humidity, rainy day, and yield of pepper for 14 years (2005 until 2018). Data analysis used the multiple linear regression analysis with the Eviews 10 software. Results: The rainfall, humidity, and rainy day simultaneous significantly increased the pepper yield of 55.767% in North Sumatra. A 1% increase in humidity can increase the pepper yield by 0.455 ton, but a 1 mm.year-1 increase in rainfall and a 1 rainy day can decrease the pepper yield in North Sumatra by 0.503 and 1.866 ton, respectively. The humidity had the value positive, meanwhile rainfall and rainy day had the value negative in pepper yield.